MONTRADO 1818-1858: DINAMIKA KOTA TAMBANG EMAS - Any Rahmayani (Patanjala: Journal of Historical and Cultural Research, 2015)
Abstrak        Penelitian ini menyajikan gambaran Kota Montrado pada 1818-1858.  Montrado,  pernah menjadi salah satu pusat kongsi pertambangan emas besar di Borneo Barat. Latar belakang penelitian ini adalah keberadaan kongsi-kongsi emas di Borneo Barat yang memegang peranan penting bagi perubahan yang terjadi di wilayah ini baik ekonomi, sosial dan politik. Permasalahan pokok yang dibahas adalah gambaran Kota Montrado dan perubahan yang terjadi seiring dengan dinamika kongsi pertambangan emas. Tujuan dari penelitian ini adalah menggambarkan proses terbentuknya Montrado sebagai pusat kongsi emas dan merekonstruksi keadaan Kota Montrado pada paruh pertama abad ke-19. Metode yang digunakan adalah metode sejarah yang terdiri atas empat tahapan: heuristik, kritik, interpretasi dan historiografi. Hasil penelitian menunjukkan bahwa Kota Montrado masa kongsi merupakan kota yang lengkap dengan pusat pemerintahan, pusat perdagangan, sarana ibadah, kelengkapan infrastruktur dan sanitasi serta wilayah-wilayah pendukung. Ekologi kota ini berubah seiring dengan runtuhnya kongsi pertambangan emas yang berpusat di wilayah tersebut. Perubahan ini dapat dilihat dari berbagai sektor seperti penurunan jumlah penduduk akibat migrasi setelah perang, runtuhnya simbol-simbol kekuasaan kongsi (thang) serta perubahan dalam organisasi pemerintahan sekaligus kemasyarakatan Tionghoa yang berganti dengan sistem yang ditetapkan pemerintah kolonial.AbstractThis study presents an overview of Montrado City between 1818 through 1858. Montrado was the major of gold mining joint venture facility in West Borneo. The background of this research is the existence of gold syndicates in West Borneo that plays an important role for the changes of economic, social and political that occurred in this region. The main problem discussed here is the image of the City of Montrado and its changes that occur in line with the dynamics of the gold mining joint venture. The aim of this study is to describe the process of formation of the joint venture Montrado as a center of gold and reconstruct the state of Montrado City in the first half of the 19th century.The method used is the historical method which consists of four stages: heuristics, criticism, interpretation and historiography. The results showed that joint venture of Montrado City was a complete city with the center of government, trade centers, places of worship, the completeness of sanitation and infrastructure. This city ecology was changed along with the collapse of the gold mining joint venture in this region. These changes can be seen from various sectors such as the decline in population due to migration after the war, the collapse of the symbols of power of joint venture (thang) as well as changes in the organization of government in the Chinese community which is replaced by a system that defined by the colonial government.